2003
DOI: 10.1128/jcm.41.5.2068-2079.2003
|View full text |Cite|
|
Sign up to set email alerts
|

Multilocus Sequence Typing and Evolutionary Relationships among the Causative Agents of Melioidosis and Glanders, Burkholderia pseudomallei and Burkholderia mallei

Abstract: A collection of 147 isolates of Burkholderia pseudomallei, B. mallei, and B. thailandensis was characterized by multilocus sequence typing (MLST). The 128 isolates of B. pseudomallei, the causative agent of melioidosis, were obtained from diverse geographic locations, from humans and animals with disease, and from the environment and were resolved into 71 sequence types. The utility of the MLST scheme for epidemiological investigations was established by analyzing isolates from captive marine mammals and birds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
344
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 455 publications
(357 citation statements)
references
References 23 publications
11
344
1
1
Order By: Relevance
“…Before the sequencing of both genomes, DNA-DNA hybridization suggested that these two species were closely related (26). A recent multilocus sequence typing study of B. pseudomallei and B. mallei isolates from around the globe has revealed that B. mallei can be considered to be a clone of B. pseudomallei (27).…”
Section: Resultsmentioning
confidence: 99%
“…Before the sequencing of both genomes, DNA-DNA hybridization suggested that these two species were closely related (26). A recent multilocus sequence typing study of B. pseudomallei and B. mallei isolates from around the globe has revealed that B. mallei can be considered to be a clone of B. pseudomallei (27).…”
Section: Resultsmentioning
confidence: 99%
“…MLSA is widely used to understand the taxonomic relationships among bacterial populations (8,10,11), and it was the method we employed in an earlier study to suggest that M. ulcerans recently evolved from M. marinum (32). To improve genome coverage and increase resolution of the MLSA method for the present investigation, we added an eighth locus to create a 3,210-bp semantide (a large information-bearing molecule).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other genetically monomorphic lineages have been accorded species status because of the distinctive diseases they cause, e.g. the causes of plague (Y. pestis [23]), anthrax (Bacillus anthracis [24]), glanders (Burkholderia mallei [25]) and tuberculosis (Mycobacterium tuberculosis [20]), although each of them corresponds to a lineage within a species of greater diversity (Yersinia pseudotuberculosis, Bacillus cereus, Burkholderia pseudomallei and the M. tuberculosis complex, respectively). Finally, still other species also have similar properties, except that a parental species has not been identified, such as the causes of leprosy (Mycobacterium leprae [14]) and Buruli ulcer (Mycobacterium ulcerans [26]).…”
Section: Introductionmentioning
confidence: 99%